Diversity Ideology: Cultural Festivals And Fusion of Diverse Socio-Ethnic Construct, Interest And Ethnic Cooperation - Dr. Aham Ikwumezie; Prof. Cosmas C. Alugbuo; Dr. (Mrs.) Chigozie Ugochukwu Okoro; Dr. Polycap Igbojiekwe (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
Cultural festivals as celebrated in Nigeria have enormous potential to drive fusion of diverse socio-ethnic construct. Our study focused on only three psychometric rationales or premise for evaluating common preference in cultural mixes. Fundamentally each ethnic group in Nigeria feels strong about the uniqueness of their culture. Distinct cultural traditions have been preserved and appreciated over history. We synthesized this construct at α = 0.05. Among others, key factors of multiculturalism (r = 0.39) (ideological condition that believe tradition must not be altered or acculturated) such as cuisines, costumes, rituals, languages did not significantly encourage fusion of socio-ethnic groups. Furthermore, among others, key factors of colorblindness (r = 0.52) (ideological condition that believe that culture has common origin “human beings” and common goals “satisfy human’s needs and desires”; and so people everywhere can bridge cultural differentia) such as local business, heritage site, Lifestyle, security correlates. However, lifestyle and security mediates in certain domains of cultural consumption that evokes fear of cultural mixing and which does not absolutely change ethnic predominant cultural mindset. Key factors of polyculturalism (r = 0.79) (ideological condition with the believe that traditions and perspectives influence each other as cultural groups continually make contact and interact) such as awareness, values, friendliness and markets appeared significant in driving fusion. Multiculturalism (p < 0.05) offers high propensity to increasing preference for cultural fusion options through increasing concerns about the impurity from the mixing elements of different socio-ethnic group